Granulosis Rubra Nasi Response to Topical Tacrolimus - Farhana Tahseen Taj; Divya Vupperla; Prarthana B. Desai (Hindawi Limited, 2017)
Granulosis Rubra Nasi (GRN) is a rare disorder of the eccrine glands. It is clinically characterized by hyperhidrosis of the central part of the face, most commonly on the tip of the nose, followed by appearance of diffuse erythema over the nose, cheeks, chin, and upper lip. It is commonly seen in childhood but it can present in adults. Here we report a case of GRN in an adult patient with very unusual histopathological presentation.